Impact Bureaucratic Structure And Legal Audit On Optimization Of Local Government Property Management - Rizkia Chudri, Intan; Desy Purnamasari; Hafifa Delly (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study aims to analyze the impact of bureaucratic structure and legal audit on the optimization of Local Government Property management in the Aceh Besar District Government. Using a quantitative approach, data were collected via questionnaires from officials across regional apparatus organizations. The findings indicate that, collectively, bureaucratic structure and legal audit exert a significant positive influence on the optimization of asset management. Furthermore, when examined individually, each independent variable also demonstrates a positive effect. A well-defined bureaucratic structure contributes to more organized and accountable management practices. Similarly, the implementation of legal audits strengthens the legal certainty of asset ownership and helps prevent disputes, thereby supporting more optimal asset utilization. The study concludes that both a sound bureaucratic framework and regular legal audits are crucial factors in enhancing the effectiveness and efficiency of local government property management